Analysis of Photovoltaic Cells Performance at University of Bangka Belitung - Andi Maulana; Welly Yandi; Wahri Sunanda (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2020)
Photovoltaic as a renewable source of electrical energy is utilized at University of Bangka Belitung (UBB) as a source of additional electrical energy. With a capacity of 280 Wp per unit, the photovoltaic performance needs to be maintained so that their performance is getting better. After cleaning with cleaning fluid, the photovoltaic voltage output has increased from 13.7 - 16.8 volt to 17.4 - 22.6 volt. After cleaning the photovoltaic, the current output also increased from 0.33 - 1.8 A to 1.5 - 7.6 A. The real power generated also increased from 4.5 - 29.7 Watt to 26 - 164 Watt